Georgia Architectural and Historic Properties Survey of Rural [291] South west section of the county, Valdosta, Ga. December 1980 - Smith and Bartholomew (South Georgia Area Planning and Development Commission, 1980)
Georgia Architectural and Historic Properties Survey of Rural [291] South west section of the county, Valdosta, Ga. December 1980. A one story rectangular plan with gabled tin roof and shiplap siding. Porch with square posts. Sash windows with 6/6 lights. Exterior chimney, transom. Brick piers. Double front doors. Date of Construction: c. 1900. A typical turn of the century house common in rural Brooks County.
Georgia Architectural and Historic Properties Survey of Rural [291] South west section of the county, Valdosta, Ga. December 1980. 1 electronic record and assets. Digitized from originals. 1 PDF. 1 scan. 1 photograph. 2400 DPI TIF. 300 DPI 4x6 JPG. 896 KB (917,799 bytes).
Keywords: Valdosta (Ga.); Historic buildings; Real property surveys; Brooks County (Ga.); Lowndes County Historical Society (Lowndes County, Ga.)